Shedding of Viable SARS-CoV-2 after Immunosuppressive Therapy for Cancer - Aydillo, Teresa; Gonzalez-Reiche, Ana S; Aslam, Sadaf; van de Guchte, Adriana; Khan, Zenab; Obla, Ajay; Dutta, Jayeeta; van Bakel, Harm; Aberg, Judith; García-Sastre, Adolfo; Shah, Gunjan; Hohl, Tobias; et al. (The New England journal of medicine, 2020)
The prolonged contagious period after viral infection in immunocompromised patients may affect how long precautions will be necessary to reduce further transmission. Replication-competent SARS-CoV-2 was detected for up to 61 days in patients who were immunocompromised by treatment for cancer.